2017
DOI: 10.5811/westjem.2017.7.34663
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Emergency Department Walkout Rate and Boarding Hours by Improving Inpatient Length of Stay

Abstract: IntroductionPatient progress, the movement of patients through a hospital system from admission to discharge, is a foundational component of operational effectiveness in healthcare institutions. Optimal patient progress is a key to delivering safe, high-quality and high-value clinical care. The Baystate Patient Progress Initiative (BPPI), a cross-disciplinary, multifaceted quality and process improvement project, was launched on March 1, 2014, with the primary goal of optimizing patient progress for adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…Moreover, the turnaround time (TAT) decreased in the five studies that addressed it. Boarding time was only evaluated in four LH interventions, with better results in all of them [ 3 , 19 , 29 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the turnaround time (TAT) decreased in the five studies that addressed it. Boarding time was only evaluated in four LH interventions, with better results in all of them [ 3 , 19 , 29 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other important outcomes reported included the percentage of day of surgery cancellations [ 8 ], reduction in surgery times [ 94 ], reduction of time to surgery [ 95 ], reduction of unnecessary instruments delivered to the OR [ 94 , 96 ], and savings in nursing time [ 97 ]. Additional measures of efficiency after LH intervention included an increase in capacity for extra patients [ 97 ], additional ED bed hours per day [ 91 ], an increase in capacity of open beds per day [ 19 , 98 ], a reduction in transfer due to lack of beds [ 29 ], improved OR utilization [ 8 , 26 , 27 ], and an increase in surgical admissions receiving appropriate perioperative antibiotics [ 86 ]. Finally, mortality was measured in six studies, four of which reported no change after LH intervention [ 17 , 18 , 28 , 29 ], while two studies reported a decreased [ 87 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations